PERAN PEMERINTAH DAERAH DALAM MEWUJUDKAN HUTAN KONSERVASI BERDASARKAN UNDANG-UNDANG NOMOR 41 TAHUN 1999 TENTANG KEHUTANAN (Studi di Kabupaten Kuningan) - Suwari Akhmaddhian (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Kuningan, local government districts declared as a conservation district. Kuningan district government coordination and cooperation with regard to conservation, namely: First, they Policy-makers need to understand how awareness of water conservation can help solve water shortage pro-blems while providing economic and social benefits, making environmental regulations that support conservation; Second, Water managers and the role of experts involved in the planning, develop-ment, and management of the water system, including managers and scientists working for the preservation of the environment is to create a reservoir as well as the urban forest in order to streng-then the conservation and Third ). Mass Media and Educators, their knowledge of the water sector may be little but they are experts in public relations, communications, marketing, and education is to create programs that support conservation programs such as Seruling (Students are concerned about the environment), Apel (Apparatus care environment) Pepeling (Bridal care for the environ-ment) and the Car Free day car-free day program. Kuningan district invites the public to play a role in realizing kuningan participate as a conservation district that is the existence of programs that support the conservation of water resources. Key words: roles, conservation, environment, government